New developments of the Z-EDM algorithm - Silva, L.M.; de Sa, J.M.; Alexandre, L.A. (Sixth International Conference on Intelligent Systems Design and Applications, 2006)
In this paper we address some open questions on the recently proposed Zero-Error Density Maximization algorithm for MLP training. We propose a new version of the cost function that solves a training problem encountered in previous work and prove that the use of a nonparametric density estimator preserves the optimal solution. Some experiments are reported comparing this cost function to the usual mean-square error and cross entropy cost functions